Strategi Berapologetika Kristen untuk Menjaga Kerukunan Umat Beragama di Indonesia - Esra Zos Samosir; Yunardi Kristian Zega; Talizaro Tafonao (STAK Reformed Remnant Internasional, 2022)
The rigidity of apologists in defending the Christian faith within the scope of religious pluralism has become a discourse. Pluralism of theology of religions creates a feeling of reluctance for apologists in defending the Christian faith so that not a few believers neglect their responsibilities in defending the Christian faith. The author tries to describe how important it is to equip and empower the laity as a strategy that can be applied in Christian apologetics to deal with pluralism of theology of religions. The purpose of writing this article is to provide awareness to community leaders and academic theologians to empower the laity in apologizing, as a strategy in dealing with attacks on Christian faith in the sphere of religious pluralism. This research was written using content analysis method. In making the laity become apologists, it is necessary to equip the congregation to have spiritual maturity, form the right motivation in conveying God's word contextually, and make disciples to the congregation.